Arabidopsis MYB24 Regulates Jasmonate-Mediated Stamen Development - Huang, Huang; Gao, Hua; Liu, Bei; Qi, Tiancong; Tong, Jianhua; Xiao, Langtao; Xie, Daoxin; Song, Susheng (Frontiers in Plant Science, 2017)
The phytohormone jasmonates (JAs) regulate various defense responses and diverse developmental processes including stamen development and fertility. Previous studies showed that JA induces CORONATINE INSENSITIVE 1-mediated degradation of JA ZIM-domain (JAZ) proteins, and activates the MYB transcription factors (such as MYB21 and MYB24) to regulate stamen development. In this study, we further uncover the mechanism underlying how MYB24 interacts with JAZs to control JA-regulated stamen development. We show that N-terminus of MYB21/24 interacts with 10 out of 12 JAZ proteins while both N-terminus and C-terminus of MYB24 are involved in dimerization of MYB21 and MYB24. Interestingly, male sterility of the JA-deficient mutant opr3 can be rescued by suitable level of the MYB24 overexpression but not by excessive high level of MYB24. Surprisingly, overexpression of MYB24NT, but not MYB24CT, could cause male sterility. These results provide new insights on MYB factors in JA-regulated stamen development.